2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Workers' Compensation [State] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
The purpose of workers' compensation is to assure quick and efficient delivery of disability and medical benefits to an injured worker and to facilitate a worker's return to gainful re-employment at a reasonable cost to the employer. This is EDIS document FE423, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.